2021
DOI: 10.3390/pathogens10101337
|View full text |Cite
|
Sign up to set email alerts
|

Seroreactivity to Coxiella burnetii in an Agricultural Population and Prevalence of Coxiella burnetii Infection in Ticks of a Non-Endemic Region for Q Fever in South Korea

Abstract: Coxiella burnetii infects humans and wild and domesticated animals. Although reported cases on Jeju Island, off the coast of South Korea, are rare, the region is considered to have a high potential for Q fever. We investigated the seroprevalence of antibodies to C. burnetii in 230 farmers living in ten rural areas on Jeju Island between January 2015 and December 2019. Blood samples were collected and examined for C. burnetii Phase I/II IgM and IgG antibodies. Trained researchers collected ticks from rural area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Ixodes ricinus infesting birds were suggested to be the vectors of C. burnetii 37 , 38 . In the ROK, C. burnetii and F. tularensis were detected more frequently in H. longicornis and H. flava ticks collected from the environmental habitats and domestic or wild animals 39 41 . However, the two pathogens were not detected in ticks infesting wild birds in this study, and the presence of these two pathogens in ticks feeding on birds in China and other southeast Asian countries located along their migration routes 21 has not been recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Ixodes ricinus infesting birds were suggested to be the vectors of C. burnetii 37 , 38 . In the ROK, C. burnetii and F. tularensis were detected more frequently in H. longicornis and H. flava ticks collected from the environmental habitats and domestic or wild animals 39 41 . However, the two pathogens were not detected in ticks infesting wild birds in this study, and the presence of these two pathogens in ticks feeding on birds in China and other southeast Asian countries located along their migration routes 21 has not been recorded.…”
Section: Discussionmentioning
confidence: 99%
“…burnetii is a tick-borne pathogen, there are only a few reports of C . burnetii in ticks in the ROK [ 108 , 109 ]. Recent studies have reported co-infections of C .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high seroprevalence of IgM or IgG (Phase I and II antibodies) to C. burnetii (35.7%) was recently reported in the rural population of Jeju Island. 11 In addition, SFTS and Q fever coinfection by tick bite was reported in South Korea in 2021. 12 …”
Section: Introductionmentioning
confidence: 99%
“…Although Q fever cases are rarely reported in this region, SFTSV and C. burnetii infection rates (IRs) in ticks on Jeju Island were analyzed in the present study based on a case of SFTS and Q fever coinfection in South Korea and the high seroprevalence of C. burnetii in agricultural population of this region. 11 12 …”
Section: Introductionmentioning
confidence: 99%